Symptoms of anxiety and worry about climate impacts among Finnish forest owners - Halonen, Jaana; Horne, Paula; Sandman, Nils; Tiittanen, Pekka; Nieminen, Veera; Hurttala, Henna; Salo, Paula; Lanki, Timo (Taylor & Francis, 2026)
Private forest owners face conflicting pressures regarding management of their forests, including
producing timber for the forest industry, preserving biodiversity, and enhancing carbon
sequestration to mitigate climate change. At the same time, climate change poses a threat to the
viability of forests. It is poorly known how these pressures affect the mental well-being of forest
owners. We used a Finnish forest owner survey (N = 1224) to examine whether distress due to
public demands regarding forest management is associated with symptoms of anxiety. We also
examined which factors are associated with worry about the climate change impacts on own
forests. Distress due to public demands on forest management was not associated with symptoms
of anxiety. Only stress due to the invasion of Russia into Ukraine was associated with symptoms of
anxiety. Having multiple objectives as a forest owner, being female gender, and having higher
education were associated with worry about the climate change impacts on own forests. In
conclusion, distress due to public demands regarding forest management may not be associated
with forest owners’ anxiety symptoms. Worry about the climate change impacts on own forests
may be partly explained by higher awareness regarding the various possibilities that forests can offer.